Length of the TM3-4 loop of the glycine receptor modulates receptor desensitization - Langlhofer, G.; Janzen, D.; Meiselbach, Heike; Villmann, C. (Neuroscience Letters, 2015)
Recent studies on the molecular determinants important for glycine receptor biogenesis and function mechanisms indicate an important role of basic residues within the intracellular loop between transmembrane domains (TM) 3 and 4. We investigate the role of loop length and loop exchange in combination with the presence or absence of basic stretches (318)RRKRR and (385)KKIDK of the human glycine receptor ?1 using expression in transfected cell lines. Exchanges of the large intracellular loop between members of the Cys-loop receptor family have been shown to keep functionality of the host receptor. Here, constructs were generated with deletion of the intracellular loop of the glycine receptor ?1, insertion of the loop from the prokaryotic Cys-loop receptor of Gloeobacter violaceus both with and without leaving the basic stretches at the N-terminal and C-terminal part of the intracellular domain. All receptor constructs were expressed at the cell surface with the significantly lowest expression of the construct with a deletion of the glycine receptor ?1 TM3-4 loop, except the two basic stretches adjoined. Functionality of the inhibitory glycine receptor chimeras was demonstrated with whole cell recordings from transfected cells. Chimeras lacking the basic stretches result in non-functionality. An analysis of receptor desensitization demonstrated that close proximity of both basic stretches resulted in large fractions of desensitizing currents. We conclude that the TM3-4 loop length is critical for glycine receptor ?1 desensitization and a direct neighborhood of both basic stretches changes receptor properties from non-desensitizing to desensitizing.
EVALuna2:26299